DESIGN OF RESIDENTIAL SAFETY SYSTEM USING E-KTP - Yudha Adi Putra; Arief Marwanto; Muhammad Qomaruddin (Journal of Telematics and Informatics, 2017)
Residential security applications by using computer technology has grown rapidly. Motion detectors, contacts on doors and windows, sirens, and a leading provider of security services for housing security management has been widely applied in electronic-based. A simple and practical use of residential security application could improve the performance efficiently and savings the cost. e-KTP card as RFID-based is used for single sign-on access on residential security areas. A reader-tag generates passively electromagnetic waves which inductances the carrier frequency of 13, 56 Mhz which produce output power around 30 dbm is assumed. In order to improved the security performance, e-KTP is integrated with software system using delphi 8.0. Theoritical results shows that a reading tag capability has measures the distance is λ = 0 cm to 2 cm has been achieved. Moreover, e-KTP is sufficient for actively sensed by reader tag. At the λ = 1 cm (0.01 m), Pt = 1 watt, therefore the received power is 0.0011 watt (0.4 dbm). This power has induced by reader tag to generate power in e-KTP. The results shows that the more distances are longer, the greater power is needed to induces e-KTP by reader tag. Keywords: e-KTP, RFID reader, Residential Security Management